Kajian Preferensi Konsumen pada Moda Transportasi Umum Kereta Api Cikuray : (Studi Kasus Trayek Cikuray Garut Kota – Pasarsenen) - Rizki Yusuf Erlangga; Lely Syiddatul Akliyah (UNISBA Press, 2023)
Abstract. Preferences can be defined as a tendency to choose something that is preferred over others, which is part of an individual's decision-making process. These preferences can be influenced by various variables. The background of this research is due to the fact that train Cikuray is one of the new transportation options for the public. Before the public uses the railway as a mode of transportation, they need to use an intermediary mode as the initial mode, and vice versa. This study aims to identify the variables that significantly influence consumer preferences, determine the initial and final modes of transportation chosen by consumers, and provide recommendations for the primary target audience of train. The research methodology employed descriptive statistics with a qualitative approach. Data processing was conducted using scoring analysis. Based on the research findings, the variable of ease of access was found to significantly influence preferences. The initial and final modes of transportation were dominated by private vehicles and online transportation, while the recommended target audience belonged to the consumer group with work and education-related activities. Abstrak. Preferensi dapat diartikan sebuah kecenderungan untuk memilih sesuatu yang lebih disukai dari pada yang lain, yang mana merupakan bagian dari pengambilan keputusan dari seorang individu. Preferensi tersebut dapat dipengaruhi oleh berbagai variabel, Latar belakang dari penelitian ini dikarenakan KA Cikuray merupakan salah satu opsi moda transportasi baru bagi masyarakat. Sebelum masyarakat menggunkan moda kereta api perlu menggunakan moda perantara sebagai moda awal, begitu pun sebaliknya. Penelitian ini bertujuan untuk mengidentikasi variabel yang sangat mempengaruhi preferensi konsumen, menentukan moda konsumen awal-akhir dan rekomendasi sasaran utama konsumen kelas KA Cikuray. Metode penelitian yang digunakan deskritif statistik dengan pendeketan kualitatif. Teknik pengolahan data dilakukan dengan menggunakan analisis skoring.